Carson, Robert John: my Army recollections (May 24 - June 22, 1984) - Carson, Robert John, 1914-1992; Bell, Chris (1984)
Interviewee: Carson, Robert John, 1914-1992; Rank: Colonel. ; ABSTRACT: Col. Robert John Carson The Corps of Royal Canadian Engineers